Design of Seaweed Liquid Waste Processing Installation in the Alkali Treatment Process as Recycled Water Based on Physics and Chemistry - Djusdil Akrim; Suparno; Muh Fikruddin; Jumadil; Nani Anggraini; Andi Zulfikar Syaiful; Hamsina; Ridwan (Jurnal Penelitian Pendidikan IPA, 2024)
World seaweed production in 2020 published by the Food and Agriculture Organization of the United Nations (FAO), Indonesia was ranked second as the largest seaweed producer with production of 11.8 million tons. The aim of this research is: To analyze the characteristics of seaweed liquid waste at PT. XYZ. To design a seaweed liquid waste processing process at PT. XYZ based on physics-chemistry as recycled water. Methods include analysis and experiments. This method is used to analyze the characteristics of liquid waste and determine the design of the seaweed liquid waste processing process at PT. XYZ. Research results: The characteristics of the seaweed liquid waste produced do not meet the quality standards in Kep.08/Men. LH/2009 concerning Industrial Waste. A physic-chemical based liquid waste processing process with neutralization, filtering and aeration can be used as recycled water in the alkali treatment process.